2019
DOI: 10.1038/s41557-019-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Back-bonding between an electron-poor, high-oxidation-state metal and poor π-acceptor ligand in a uranium(v)–dinitrogen complex

Abstract: Back-bonding between an electron-poor, high-oxidationstate metal and poor -acceptor ligand in a uranium(V)-dinitrogen complex . Back-bonding between an electron-poor, high-oxidation-state metal and poor -acceptor ligand in a uranium(V)-dinitrogen complex. Nature Chemistry,11,[806][807][808][809][810][811] Back-bonding between an electron-poor, high-oxidation-state metal and poor π-acceptor ligand in a uranium(V)-dinitrogen complex Abstract A fundamental bonding model in coordination and organometallic chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
0
44
0
Order By: Relevance
“…Although uranium-based inorganic materials were shown to be active catalysts of the Haber–Bosch process for the N 2 conversion to ammonia, an iron-based catalyst was adopted for industrial production of ammonia. As a result, the dinitrogen chemistry of molecular uranium compounds is significantly less developed than d-block metals and mostly involves labile N 2 binding or two-electron N 2 reduction, with only three examples of four-electron N 2 reduction reported recently (complexes A – C in Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Although uranium-based inorganic materials were shown to be active catalysts of the Haber–Bosch process for the N 2 conversion to ammonia, an iron-based catalyst was adopted for industrial production of ammonia. As a result, the dinitrogen chemistry of molecular uranium compounds is significantly less developed than d-block metals and mostly involves labile N 2 binding or two-electron N 2 reduction, with only three examples of four-electron N 2 reduction reported recently (complexes A – C in Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen, like ethylene, also has a molecular weight of 28 Da, and is present in abundance during the ESI-MS experiment thanks to its use as a desolvation gas, and was a possible explanation for this ion. While many dinitrogen complexes have been reported for metal centers in Groups 3-9, some simple, [267][268][269][270][271] some with carefully constructed coordination environments, [272][273][274][275][276][277][278][279][280] and others evolved for nitrogen fixation, [281][282][283][284][285] such complexes are less common in Groups 10 and 11. Isolated dinitrogen complexes involving platinum are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] In addition, molecular uranium systems also exhibit attractive ability for N 2 binding,r eduction, and activation. [36][37][38][39][40][41][42][43][44][45][46] Fori nstance,M azzanti and coworkers reported that the multimetallic diuranium(III) complex [K n {[U(OSi(O t Bu) 3 ) 3 ] 2 (m-E) (E = N, O) is capable of activating N 2 to N 2 4À via af our-electron reduction process. [43,44] Arnold and co-workers found that the four-electron reduction of N 2 was also achieved by the thorium or uranium dinuclear metallacycles,M 2 (mTP) 2 (mTP = [{2-(OC 6 H 2 -t Bu-2,Me-4) 2 CH}-C 6 H 4 -1,3] 4À ;M = U, Th)i nt he presence of as trong reductant (KC 8 ).…”
Section: Introductionmentioning
confidence: 99%